Crevice corrosion behavior of X70 steel in NaCl solution with different pH. (15th April 2021) - Mu, J.; Li, Y.Z.; Wang, X.
Highlights: Crevice corrosion could be initiated in pH = 2 and pH = 12 solution. Crevice corrosion could not occur in pH = 6.8 solution. The rise of pH and Cl − inside crevice lead to crevice corrosion in pH = 2 solution. The rise of H + and Cl − inside crevice lead to crevice corrosion in pH = 12 solution. The decrease of OCP outside crevice erases galvanic corrosion in pH = 6.8 solution. Abstract: The crevice corrosion of X70 steel in 0.34 mol/L NaCl solution with different pH was investigated. The crevice corrosion could be initiated in pH = 2 and pH = 12 solution and it could not occur in pH = 6.8 solution. The increase of pH and Cl − inside crevice are responsible to crevice corrosion in pH = 2 solution. However, the decrease of pH and increase of Cl − inside crevice contribute to crevice corrosion in pH = 12 solution. The negative shift of OCP of steel outside crevice results in the disappearance of galvanic corrosion and then crevice corrosion could not occur in pH = 6.8 solution.